7C.04: DIAGNOSTIC VALUE OF PRESSURE WAVEFORM BASED ANALYSIS FOR IMPAIRED SYSTOLIC FUNCTION. (June 2015) - Hametner, B.; Wassertheurer, S.; Parragh, S.; Eber, B.; Weber, T.
Abstract : Objective: We recently developed and validated a technique to separate the forward and backward components of the arterial pulse, based on pressure waves alone. While we found the results useful in the workup of heart failure with preserved ejection fraction, little is known about the diagnostic yield in patients with impaired systolic function. Design and method: Based on non-invasive radial waveforms from tonometry and a Windkessel model derived flow signal, we quantified the forward and backward waves in the aorta of 61 patients with severly reduced systolic function (rEF) and 122 controls with normal ejection fraction, matched for age, gender, and brachial blood pressures. Forward waves were quantified, using wave intensity analysis, resulting in systolic S-wave (increasing pressure and flow) and systolic D-wave (decreasing pressure and flow). Backward waves were quantified, using pulse wave analysis, resulting in Augmentation Index (AIx) and Pressure Augmentation (AP). Ejection duration was indexed to heart rate (LVETI). In addition, QRS duration from 12 lead ECGs was measured and normalized for heart rate, using the formula QRSc = QRS / sqrt(RR-interval). Results: For the same levels of brachial blood pressures, rEF was associated with shorter LVETI, lower S / D ratio, and lower AIx and AP. Based on ROC curve analysis, AUCs for the detection of rEF for LVETI, AIx, AP, and S/D ratio were 0.81, 0.73, 0.7, and 0.83, respectively (p < 0.0001 for all). Combining LVETI with AIx and S/D R increased AUC to 0.86 (CI 0.80–0.91). Adding QRSc significantly (p = 0.003) increased AUC to 0.94 (CI 0.89–0.97) and lead to a correct classification of 89.5% of the patients, see figure. Conclusions: Characteristics of the pressure waveform, which potentially can be derived from oscillometric cuffs with automated algorithms, may help in the diagnosis of patients with impaired systolic function. Adding simple ECG characteristics significantly improves the prediction model. Ultimately, oscillometric blood pressure cuff-derived measures may indicate the need for further investigations, e.g. echocardiography. Figure. No caption available.